The effect of nitrogen fertilization and annual burning of bluestem pastures on cows, calves, and vegetation - Woolfolk, J.S.; Schalles, R.R.; Harbers, L.H.; Allen, Leland James; Smith, E.F.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Six native Bluestem pastures and spring-calving cows were used to evaluate effects of burning and fertilizing pastures. Two pastures were controls, two were burned, and two were burned and fertilized with 40 pounds of urea nitrogen an acre applied aerially. Average daily gain of the calves did not differ significantly among pastures. Pounds of beef produced per acre was significantly higher from the burned, fertilized pastures, which supported heavier stocking rates with increased herbage production.
Keywords: Beef; Nitrogen; Burning; Bluestem pastures; Cows; Calves; Vegetation